2017
DOI: 10.3917/th.801.0051
|View full text |Cite
|
Sign up to set email alerts
|

Towards real-time detection of cognitive effort in driving: contribution of a cardiac measurement

Abstract: In 2013, attention deficits accounted for 40 to 50 % of injury accidents. Recent studies have succeeded in detecting impaired states of attention, with a view to assisting the driver, and provide a new opportunity to increase road safety. This study focuses on the detection of drivers' cognitive effort and seeks, through the study of heart rate change (HRC), to identify a sensitive indicator of cognitive effort in short time windows. Eighteen young drivers participated in the study and took part in 8 experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…In order to minimize the influence of the driving scenario position and driving style, the considered mean values take into consideration only 6 s [following the parameters employed in Pépin et al (2017)] after every stimulus presentation and averaged for all the task duration.…”
Section: Methodsmentioning
confidence: 99%
“…In order to minimize the influence of the driving scenario position and driving style, the considered mean values take into consideration only 6 s [following the parameters employed in Pépin et al (2017)] after every stimulus presentation and averaged for all the task duration.…”
Section: Methodsmentioning
confidence: 99%
“…This switchover could have a cost in terms of attentional resources. Yet, a recent study has showed the feasibility of detecting the cognitive effort generating by a cognitive demand of a task through heart rate measurement (Pepin et al, 2017). It appears that the specific pattern found here after participants self-reported their MW episodes could correspond to a cognitive effort pattern.…”
Section: Cardiac Datamentioning
confidence: 69%
“…Heart Rate (HR) values were computed using equations provided by Roy, (2015) and illustrated by Pepin et al, (2017). From the cardiac signal, several time-domain indices bringing information about heart rate variability have been calculated from IBI such as the Root Mean Square Successive Differences of NN intervals (RMSSD) and proportion of the number of interval differences of successive NN intervals greater than 50 ms (pNN50).…”
Section: Cardiac Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that task demand refers to the intrinsic features of the task while task load describes the subjective impact on the operator [6] and refers to the perceived relationship between the amount of mental processing capability or resources and the amount of resources required by the task. Therefore, measuring workload requires taking into account factors characterizing the task and factors describing how the driver engages in and allocates his/her resources for the processing of the task [47]. In the resource perspective, the level of the driver skill, e.g.…”
Section: Introductionmentioning
confidence: 99%